2005
DOI: 10.1080/00071660500066233
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of feeding treatments and lighting on age at first egg and subsequent laying performance and carcase composition of broiler breeder hens

Abstract: The effects of the growth curve from 15 to 20 weeks, age at photostimulation and pattern of photostimulus on sexual maturity, egg production and egg weight were evaluated in two trials with broiler breeder females to 56 and 34 weeks of age (housed in litter pens and individually caged, respectively). Carcase composition and reproductive morphology of hens varying in laying efficiency were measured in the second trial. Trial 1: Four growth curves were applied from 15 to 20 weeks to pullets housed in litter pens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…The maturation interval for the 21WK treatment in the current study is comparable to these results, but the maturation interval of the 18WK treatment is much larger. Previously, hypotheses were proposed that the rate of sexual maturation after photostimulation increases, when photostimulation occurred later, such that for every day that photostimulation was delayed, AFE was delayed between 0.21 and 0.40 d (Yuan et al, 1994 ; Robinson et al, 1996 ; Renema et al, 2001b ; Joseph et al, 2002 ; Ciacciariello and Gous, 2005 ; Pishnamazi et al, 2014 ). However, in the current study, AFE was advanced by 19 d when photostimulation was delayed by 21 d, resulting in an advance of 0.90 d for every day that photostimulation was delayed.…”
Section: Resultsmentioning
confidence: 99%
“…The maturation interval for the 21WK treatment in the current study is comparable to these results, but the maturation interval of the 18WK treatment is much larger. Previously, hypotheses were proposed that the rate of sexual maturation after photostimulation increases, when photostimulation occurred later, such that for every day that photostimulation was delayed, AFE was delayed between 0.21 and 0.40 d (Yuan et al, 1994 ; Robinson et al, 1996 ; Renema et al, 2001b ; Joseph et al, 2002 ; Ciacciariello and Gous, 2005 ; Pishnamazi et al, 2014 ). However, in the current study, AFE was advanced by 19 d when photostimulation was delayed by 21 d, resulting in an advance of 0.90 d for every day that photostimulation was delayed.…”
Section: Resultsmentioning
confidence: 99%
“…02 and 0 . 04 of all eggs laid between 25 and 60 weeks and Ciacciariello & Gous (2005) reported a rate of approximately 0 . 04 from 23 to 56 weeks.…”
Section: Double-yolked Eggsmentioning
confidence: 99%
“…Although environmental factors such as body weight, body composition as well as age are critical for the onset of sexual maturity [1-4], but the trait is also determined by its genetic components. Studies of human showed that 50%-80% of the variation in pubertal timing is determined by genetic factors [5,6].…”
Section: Introductionmentioning
confidence: 99%